THE BLACK BOX: Demystifying the Study of Korean Unification and North Korea. - Hastings, Justin V. (Pacific Affairs (Pacific Affairs), 2025)
The article discusses the significance of historical and contemporary issues surrounding Japanese imperial assimilation and North Korean dynamics, as explored in two separate works. The first part highlights Kang's examination of Japanese assimilation discourse, particularly its impact on the Zainichi community, through the lens of Yu Miri’s novel, which challenges existing notions of ethnic identity. The second part reviews Victor D. Cha's book, "The Black Box," which aims to demystify North Korea and Korean unification by analyzing various aspects such as military relations, cyber capabilities, and market participation within North Korea. Cha's work emphasizes the importance of understanding North Korea's external actions and the evolving perceptions of unification among South Koreans and experts.